TRANSFORMASI PARADIGMA MISI KRISTEN DALAM MASYARAKAT MAJEMUK: DARI EKSKLUSIVISME MENUJU INKLUSIVISME - Tintingon, Angel Ribka; Suoth, Vanny Nancy (Sekolah Tinggi Teologi Injili Indonesia Ambon, 2025)
This article examines the transformation of the Christian mission paradigm from exclusivism to inclusivism within the context of pluralistic societies. The purpose of the study is to analyze how the church can shift the exclusive mindset of believers so that they are able to live and witness in an inclusive, open, and contextually relevant manner amidst social and cultural diversity. This research employs a qualitative method with a descriptive approach, including literature review on missiology, observation of pluralistic communities, and theological analysis of the concept of Missio Dei and mission practices in diverse societies. The findings indicate that exclusivism, while affirming the truth of the faith, can lead to closed-minded attitudes, discrimination, and social conflict. In contrast, the inclusivist paradigm emphasizes the church’s participation in God’s universal work, integrating the proclamation of the Gospel with spiritual education, interfaith dialogue, and cross-community social activities. This transformation of mindset not only strengthens the witness of faith but also positions the church as an agent of reconciliation, peace, and social transformation relevant to pluralistic societies. This study contributes to the field of missiology by offering a new perspective on the importance of inclusivism as a strategy for contemporary Christian mission.